Broadband miniaturised bow‐tie antenna for 3D microwave tomography. Issue 4 (1st February 2014) - Jalilvand, M.; Li, X.; Kowalewski, J.; Zwick, T.
Abstract : A broadband, miniaturised bow‐tie antenna array element designed to be used in three‐dimensional (3D) microwave imaging systems based on the tomographic approach is proposed. Miniaturisation is achieved by adding inductive strips to the capacitive antenna element and thereby lowering the cutoff operational frequency. Furthermore, the broadband directive radiation characteristic of the antenna with the proposed feeding network is equivalent to that of the same antenna being fed by an ideally symmetrical feeding network. This characteristic assists in the modelling of the antenna in the numerical solver. The proposed broadband antenna covering 0.85–3.25 GHz is a compact, directive element with a simple structure having the potential to be implemented in the numerical solver in 3D microwave tomography without imposing a high computational cost on the solver.